A synonymous KCNH2 polymorphism and methadone trough level influence QTc prolongation in Kelantanese Malay recipients of methadone maintenance therapy (MMT) in Malaysia - Muhammad Irfan Abdul Jalal; Muhammad-Redha Abdullah-Zawawi; Nurfadhlina Musa; Basyirah Ghazali; Zalina Zahari; Nasir Mohamad (PLoS ONE, 2025)
Potassium voltage-gated channel subfamily H member 2 (KCNH2) polymorphisms have been found to influence the heart-rate adjusted QT (QTc) intervals. We investigated the association between KCNH2 polymorphisms and QTc intervals among Malay opioid-dependent methadone maintenance treatment (MMT) recipients. A cross-sectional study was conducted involving 111 patients with stable methadone dosage for at least 6 months attending several methadone clinics in Kelantan, Malaysia between March 2011 and October 2012. Those with cardiac structural defects, recipients of other QTc-prolonging pharmacotherapeutic agents, had aggressive behavior or other active psychiatric illnesses, chronic medical and surgical ailments and who were unable to communicate in Malay and English were excluded. The Fridericia-corrected QTc intervals were recorded using a 12-lead electrocardiogram. DNA samples were extracted from peripheral blood leukocytes and genotyped using nested allele-specific polymerase chain reaction for these four KCNH2 polymorphisms: 1539C > T, 1956T > C, 2350C > T, and 2690A > C. Mean QTc interval is 408 ms (SD: 24). Molecular docking was performed on all four KCNH2 polymorphisms to investigate the impact of the nucleotide changes on methadone binding. Based on multiple regression analysis, only 1539T > C polymorphism (βadjusted: 10.506 (95% CI:0.846, 20.166), p = 0.033; recessive model), serum methadone trough (βadjusted: 0.025 (95% CI: 0.006, 0.043), p = 0.009), potassium (βadjusted: -8.756 (95% CI: -15.938, -1.575), p = 0.017) and magnesium (βadjusted: -106.226 (95% CI: -159.291, -53.161), p < 0.001) levels were significantly associated with mean QTc. Molecular docking analysis resulted in good binding-energy values between the 1539C > T and methadone, with the formation of hydrophobic and π–π stacking interactions, suggesting that 1539C > T was the newly discovered SNP involved in QTc prolongation. In conclusion, the 1539C > T KCNH2 polymorphism is associated with QTc prolongation in our MMT recipients, necessitating QTc monitoring to prevent methadone-associated cardiotoxicity in this Malay MMT population.